Evaluating the Effect of a Patient Decision Aid for Atrial Fibrillation Stroke Prevention Therapy. Issue 7 (July 2019) - Loewen, Peter S.; Bansback, Nick; Hicklin, James; Andrade, Jason G.; Kapanen, Anita I.; Kwan, Leanne; Lynd, Larry D.; McClean, Alison; MacGillivray, Jenny; Salmasi, Shahrzad
Background: Stroke prevention therapy decisions for patients with atrial fibrillation (AF) are complex and require trade-offs, but few validated patient decision aids (PDAs) are available to facilitate shared decision making.Objective: To evaluate the effects of a novel PDA on decision-making parameters for AF patients choosing stroke prevention therapy.Methods: We developed an evidence-based individualized online AF PDA for stroke prevention therapy and evaluated it in a prospective observational pilot study. The primary outcome was decisional conflict. Secondary outcomes were knowledge, usability/acceptability, patient preferences, effects on therapy choices, and participant feedback.Results: 37 participants completed the PDA. The PDA could be completed independently and was well accepted. It significantly decreased the mean decisional conflict score ( P < 0.001) and all its subscales and increased participant AF knowledge ( P = 0.02). 76% of participants indicated that their individualized therapy attribute ranking was congruent with their values. The PDA-generated best-match therapy was chosen by 70% of participants in decision 1 (no therapy, aspirin, or oral anticoagulant), and 17% for decision 2 (choice of anticoagulant). Among AF patients, 60% chose a different drug than that currently prescribed to them.Conclusion and Relevance: Our PDA was effective for reducing decisional conflict, increasing patient knowledge, eliciting patients' values, and presenting therapy options that aligned with patients' values and preferences. Using the PDA revealed that many patients have therapy preferences different from their currently prescribed treatment. The PDA is a practical and potentially valuable tool to facilitate decision making about stroke prevention therapy for AF.